Informant Discrepancies and the Heritability of Antisocial Behavior: A Meta-Analysis - Karabatsos, George (2013)
Antisocial behavior, which includes both aggressive and delinquent activities, is the opposite of prosocial behavior. Researchers have studied the heritability of antisocial behavior among twin and non-twin sibling pairs from behavioral ratings made by parents, teachers, observers, and youth. Through a meta-analysis, we examined longitudinal and cross sectional research in the behavioral genetics of antisocial behavior, consisting of 42 studies, of which 38 were studies of twin pairs, 3 were studies of twins and non-twin siblings, and 1 was a study of adoptees. These studies provided n = 89 heritability (h2) effect size estimates from a total of 94,517 sibling pairs who ranged in age from 1.5 to 18 years; studies provided data for 29 moderators (predictors). We employed a random-effects meta-analysis model to achieve three goals: (a) perform statistical inference of the overall heritability distribution in the underlying population of studies, (b) identify significant study level moderators (predictors) of heritability, and (c) examine how the heritability distribution varied as a function of age and type of informant, particularly in longitudinal research. The meta-analysis indicated a bimodal overall heritability distribution, indicating two clusters of moderate and high heritability values, respectively; identified four moderators that predicted significant changes in mean heritability; and indicated differential patterns of median h2 and variance (interquartile ranges) across informants and ages. We argue for a cross-perspective, cross-setting model for selecting informants in behavioral genetic research, that is flexible and sensitive to changes in antisocial behavior over time.Comment: 72 pages, 3 figures, 2 tables; As of 2.15.2013 this manuscript is under review for publication. Please do not cite without written permission from the lead author. Thank you